ANALISIS TIPOGRAFI PADA LOGO SECRET GARDEN VILLAGE - Alicia Alfia Asokawati; Md. Wira Putra Dananjaya (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
This study presents a review of typographic analysis on the Secret Garden Village logo based on typographic principles, namely readability, legibility, visibility and clarity. Understanding the importance of typography in creating a strong visual identity is achieved by reviewing relevant literature. The analysis method used is descriptive analysis of typographic principles to typographic elements in the logo such as font type, size, letter spacing and color. Based on the analysis result, this tourist destination logo consists of typographic elements representing the name and origin of the destination, while its graphic element in the form of trailing leaf accent. The font type used in the typographic elements is Cinzel Decorative Bold with the chosen colors being golden yellow and tosca green. The typographic elements in this logo have successfully applied typographic principles, making the message easily understood by readers. Overall, this logo effectively represents a strong identity.